The Role of Brand Attachment to the Antecedents of Brand Passion - Rayhan Nygel Putra Bilondatu; Miharni Tjokrosaputro (International Journal of Application on Economics and Business, 2023)
Indonesia's fashion sector has recently seen remarkable growth. The rise of several local brands that drawing attention of the public, particularly the younger generation, is indicative of this. This study was conducted to determine how brand passion, mediated by brand attachment, is affected by brand image self-congruity and social media content marketing. Self-congruity variable was assessed by using the dimension of actual self- congruity, ideal self-congruity, and social self-congruity. At the same time, content marketing has been measured by user-generated content and firm-created content. This quantitative research used the data gathered from questionnaire distribution through Google Form. The number of samples is 290. Data manipulation and testing used the SmartPLS version 3. The results showed that self-congruity and content marketing positively affect brand passion through brand attachment. Moreover, the results of this study also prove that content marketing could directly affect brand passion.